2013
DOI: 10.1007/s00737-013-0344-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of general anxiety and childbirth-specific anxiety on birth outcome

Abstract: In the present study, we examined a German sample to determine whether anxiety symptoms during pregnancy had an impact on the duration and method of childbirth. Data of N = 88 women recruited at the Heidelberg University Hospital were used in the analyses. Prepartum anxiety symptoms were assessed with the State-Trait Anxiety Inventory (STAI, general anxiety) and the Pregnancy Related Anxiety Questionnaire (PRAQ-R, pregnancy-specific anxiety). Obstetric outcome was taken from birth records and operationalized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
74
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 26 publications
10
74
1
8
Order By: Relevance
“…She also observed that women with high levels of fear opted for childbirth with epidural anesthesia, while women with low levels of fear preferred natural childbirth. Similar results were also observed in the studies conducted by Reck et al [6] and Beebe et al, [7] who found a significant positive correlation between the overall anxiety level and birth-related anxiety, a significant negative correlation between the anxiety level and self-efficacy level in coping with childbirth, and a significant negative correlation between ways of coping with the childbirth process and the level of pain during childbirth. There was also a correlation between fear of childbirth, self-efficacy and the type of childbirth.…”
Section: Introductionsupporting
confidence: 78%
“…She also observed that women with high levels of fear opted for childbirth with epidural anesthesia, while women with low levels of fear preferred natural childbirth. Similar results were also observed in the studies conducted by Reck et al [6] and Beebe et al, [7] who found a significant positive correlation between the overall anxiety level and birth-related anxiety, a significant negative correlation between the anxiety level and self-efficacy level in coping with childbirth, and a significant negative correlation between ways of coping with the childbirth process and the level of pain during childbirth. There was also a correlation between fear of childbirth, self-efficacy and the type of childbirth.…”
Section: Introductionsupporting
confidence: 78%
“…These researchers http recommended that estimation of pregnancy-specific anxiety benefit in identification and risk reduction more specifically (Bayrampour, Heaman, Duncan, & Tough, 2013;Huizink et al, 2004;Rauchfuss & Maier, 2011;Reck et al, 2013). With limited evidences available on specific fears and worries related to pregnancy, the structure of pregnancy anxiety and its impact on pregnancy outcomes necessitate further studies exploring pregnancy-specific anxieties and its risk factors.…”
Section: Introductionmentioning
confidence: 95%
“…Pregnancy anxiety, or anxiety regarding a current pregnancy, has been fairly consistently associated with shorter gestation and preterm birth, in rates comparable to other known risk factors such as medical and obstetric risks and smoking (Dunkel Schetter 2012). Pregnancy anxiety has also been associated with higher rates of emergency Caesarean sections in one study (Ryding 1998) but not others (Reck 2013), and longer duration of labour (Reck 2013). …”
Section: Anxiety Disordersmentioning
confidence: 89%